Searching on the Back: Attentional Selectivity in the Periphery of the Tactile Field - Gherri, Elena; White, Felicity; Ambron, Elisabetta (Frontiers in Psychology, 2022)
Recent evidence has identified the N140cc lateralized component of event-related potentials as a reliable index of the deployment of attention to task-relevant items in touch. However, existing ERP studies have presented the tactile search array to participants’ limbs, most often to the hands. Here, we investigated distractor-interference effects when the tactile search array was presented to a portion of the body that is less lateralized and peripheral compared to the hands. Participants were asked to localize a tactile target presented amongst distractors in a circular arrangement to their back. The N140cc was elicited contralateral to the target when the singleton distractor was absent. Its amplitude was reduced when the singleton distractor was present and contralateral to the target, suggesting that attention was directed at least in part to the distractor when the singletons are on opposite sides. However, similar N140cc were observed when the singleton distractor was ipsilateral to the target compared to distractor absent trials. We suggest that when target and singleton distractor are ipsilateral, the exact localization of the target requires the attentional processing of all items on the same side of the array, similarly to distractor absent trials. Together these observations replicate the distractor-interference effects previously observed for the hands, suggesting that analogous mechanisms guide attentional selectivity across different body parts.